2020
DOI: 10.3390/met11010067
|View full text |Cite
|
Sign up to set email alerts
|

Cooling under Applied Stress Rejuvenates Amorphous Alloys and Enhances Their Ductility

Abstract: The effect of tensile stress applied during cooling of binary glasses on the potential energy states and mechanical properties is investigated using molecular dynamics simulations. We study the three-dimensional binary mixture that was first annealed near the glass transition temperature and then rapidly cooled under tension into the glass phase. It is found that at larger values of applied stress, the liquid glass former freezes under higher strain and its potential energy is enhanced. For a fixed cooling rat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Here, we highlight a recent discovery that thermal cycling between the room and cryogenic temperatures can lead to rejuvenation of metallic glasses due to heterogeneous thermal expansion [7][8][9][10][11][12][13][14][15][16][17][18]. Remarkably, it was also recently demonstrated experimentally and by means of atomistic simulations that cooling across the glass transition temperature under applied stress rejuvenates amorphous alloys and increases their ductility [19,20]. However, despite extensive efforts aimed at exploring the operational parameter space in order to extend the range of glassy state, the optimization of processing routes remains a difficult task.…”
Section: Introductionmentioning
confidence: 75%
“…Here, we highlight a recent discovery that thermal cycling between the room and cryogenic temperatures can lead to rejuvenation of metallic glasses due to heterogeneous thermal expansion [7][8][9][10][11][12][13][14][15][16][17][18]. Remarkably, it was also recently demonstrated experimentally and by means of atomistic simulations that cooling across the glass transition temperature under applied stress rejuvenates amorphous alloys and increases their ductility [19,20]. However, despite extensive efforts aimed at exploring the operational parameter space in order to extend the range of glassy state, the optimization of processing routes remains a difficult task.…”
Section: Introductionmentioning
confidence: 75%
“…Moreover, the process of rejuvenation during elastostatic compression can be accelerated when stress is temporarily applied along alternating directions [22,23]. In addition, it was also recently demonstrated experimentally and by means of molecular dynamics (MD) simulations that higher energy states can be realized via rapid freezing of a glass former under applied stress [24,25]. However, in spite of the progress made, the design of novel strategies for thermomechanical processing of metallic glasses is required to access a broader range of energy states and improved mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Several rejuvenating methods have been proposed by researchers to improve the energy state and the ductility of amorphous alloys [10][11][12][13][14] . Among them, external elastic loading without any macroscopic alteration of bulk sample is one of the favored techniques, tuning the mechanical properties and plasticity [15][16][17][18] . To provide some examples, Samavatian et al [19][20][21] indicated that the tensile elastostatic loading leads to the significant disordering of short-and medium-atomic arrangements and induces the structural rejuvenation in the Zr-based BMGs.…”
Section: Introductionmentioning
confidence: 99%